Valuation of EU Agricultural Landscape - Pavel Ciaian; Sergio Gomez y Paloma (Economics and Econometrics Research Institute (EERI), 2011)
The present paper provides a meta-analysis of agricultural landscape valuation studies and through the estimated benefit transfer function it projects the value of EU landscape. The analyses are based on information from more than thirty European and non-European studies which use a stated preference approach to uncover society's willingness to pay (WTP) for agricultural landscape. Our calculations show that, the WTP in the EU varies between 134 and 201 exteuro/ha with an average value of 149 exteuro/ha in 2009. Furthermore the calculations indicate that the total value of EU landscape in 2009 is estimated to be in the range of exteuro24.5 – 36.6 billion per year, with an average of exteuro27.1 billion, representing around 8 percent of the total value of EU agricultural production and roughly half of the CAP expenditures.
Keywords: H23; H31; Q12; Q51; Q57; 330; Agricultural landscape; valuation; willingness to pay; meta-analysis; benefit transfer